Usefulness of the CHA2DS2-VASc and HAS-BLED Scores in Predicting the Risk of Stroke Versus Intracranial Bleeding in Patients With Atrial Fibrillation (from the FibStroke Study) - Samuli Jaakkola; Tuomas O. Kiviniemi; Ilpo Nuotio; Juha Hartikainen; Pirjo Mustonen; Antti Palomäki; Jussi Jaakkola; Antti Ylitalo; Päivi Hartikainen; K.E. Juhani Airaksinen (Elsevier, 2022)
CHA2DS2-VASc and HAS-BLED scores stratify the risk of thromboembolic and bleeding events respectively in patients with atrial fibrillation. There is only little information on how they differentiate which of the 2 clinically most important complications (ischemic stroke [IS] or an intracranial bleeding [IB]) the patient is more prone to suffer.We evaluated both scores in patients with either of these major complications. The FibStroke Study collected data on all patients with atrial fibrillation with either an IS or an IB event between 2003
and 2012 in 4 Finnish hospital districts. Individual electronic patient records were manually reviewed to collect the study data. To assess the relative risk of IS and IB, an IS/IBratio was calculated by dividing the absolute number of ISs with the absolute number of IBs within each score category. A total of 3,816 (82.7%) ISs and 798 (17.3%) IBs were detected in 3,909 patients. In general, ISs occurred more often than IBs in patients on oral anticoagulation in each score category (ratio 1.6 to 5.1). The ratio decreased below 1, however,
only with very high HAS-BLED scores (>4). Moreover, 221 ISs and 53 IBs occurred in patients with HAS-BLED > CHA2DS2-VASc, of whom only 19.7% were on anticoagulation. In conclusion, IS was the predominant intracranial event irrespective of CHA2DS2-VASc score, HAS-BLED score ≤4, or use of oral anticoagulation, also in patients with low estimated thromboembolic risk (CHA2DS2-VASc 0 to 1). Furthermore, the HAS-BLED score predicted the excess of IBs over ISs only at very high-risk levels.